متطلبات تحسين جودة التعليم المحاسبي في الجزائر: دراسة قياسية - درويش، عمار (جامعة عبد الحميد بن باديس مستغانم - مخبر ديناميكية الاقتصاد الكلي والتغيرات الهيكلية دينامكس, 2017)
يهدف هذا البحث إلى تبيان أهمية مؤسسات التعليم المحاسبي في توفير محاسبين مهنيين قادرين على ولوج عالم الشغل، وذلك بكفاءات تمكنهم من مواجهة تحديات التغير السريع في بيئة الأعمال ومعالجة المشكلات الاستثنائية، ولعل التعليم الجامعي يعتبر الركن الأساسي للوفاء بمتطلبات سوق العمل، وهذا من خلال تكوين الطلاب وفتح التخصصات التي تعنى بالتكوين والتأهيل في مختلف فروع العلوم المحاسبية والمالية. فمن خلال هذا البحث تبين لنا أن هناك ضرورة لإعادة النظر في برامج التعليم المحاسبي في الجزائر، وتطوير مضامينه لتتوافق وتوصيات الاتحاد الدولي للمحاسب (IFAC)، وتوسيع ثقافة التعليم المحاسبي بإنشاء تخصصات جديد، ومراكز ومعاهد تعليم حديثة تعني بالتكوين المحاسبي، بالإضافة إلى تيسير دخول عالم مهنة المحاسبة بإصدار قوانين واضحة تنظم المهنة وتفعيل تطبيقها.
The aim of this research is to identify the importance of accounting education in providing professional accountants able to enter the world of jobs efficiently, which would enable them to confront the changes and the challenges of rapid change in the business environment and addressing the exceptional issues, and perhaps university education is the cornerstone to fulfill the requirements of the job market during the formation of the students and the opening of specialties concerned with the training and qualification in the various branches of accounting and financial sciences. Through this research we have found that there is a necessity to reconsider the accounting education programs in Algeria and the development of its contents to correspond to the recommendations of the International Union of Accounting Education, and expanding the culture of accounting education by creating a new specialties, centers and institutes of modern education concerned with accounting as well as to facilitate the entry to the world of the accounting profession by issuing clear laws regulating the profession and activate its application.
Keywords: التعليم المحاسبي -- إدارة الجودة الشاملة -- التأهيل المحاسبي -- الجزائر